A study on the fluorescence property of the perylene derivatives with methoxy groups. (January 2018) - Kim, Jeong Yun; Woo, Sung Wun; Namgoong, Jin Woong; Kim, Jae Pil
Abstract: Perylene-based dyes with methoxy groups at various positions were synthesized to understand the effect of the methoxy groups on the fluorescence quenching. Additionally, perylene-based dyes with ethyl groups in place of the methoxy groups were also synthesized to serve as control. Absorption and fluorescence properties of the dyes were measured, and then, density functional theory (DFT) and time-dependent density functional theory (TD-DFT) simulations were conducted. The methoxy groups of terminal-substituents had a lesser effect on fluorescence quenching than the methoxy groups of bay-substituents. Moreover, only the methoxy groups at the para-position of the bay-substituents strongly affected on fluorescence quenching. These results showed that the fluorescence of the dyes are influenced by the electron donating effect of the methoxy groups when the methoxy groups are involved in the main conjugation systems of the dyes. Graphical abstract: Highlights: Perylene-based dyes with methoxy groups at various positions are synthesized. Absorption, fluorescence properties and TD-DFT simulations of the dyes are studied. Only the methoxy groups at the para-position of bay-substituents inhibit the fluorescence of dyes. The methoxy groups have to be involved in the conjugation system of the dyes for the fluorescence quenching.